A Firm- and Demand-side Perspective on Behavioral Strategy for Value Creation: Insights from the Hearing Aid Industry - Matilde Fogh Kirkegaard (Copenhagen Business School (CBS), 2018)
Through an investigation of individual decision-making behavior and the impact it has on the perceived value of innovation, this thesis offers novel perspectives on key strategic management issues. We demonstrate how the value of innovation, when identified as a subjectively realized value by the consumer, specifically, perceived product benefits, can help identify the role of individual decision-making as well as behavioral factors guiding value creation of innovation. In the intersection between behavioral science and strategic management of innovation, these insights take the perspective of both the firm-side and demand-side of a value chain by identifying innovation performance as value created at the levels of the manufacturer, the salesperson and the consumer. Hence, this thesis contributes to the strategic management literature on innovation and value creation by answering the following research question: To what extent do decision-making heuristics at the individual level affect value creation at the firm-side and the demand-side of the value chain, and what management practices can facilitate decision-making for improved value creation? By attending to both the manufacturer and product market, the three papers constituting this thesis identify opportunities to augment value creation by exploring whether systematic behavioral bounds determine the likelihood of innovations to fulfill firms' expectations for innovation performance. The thesis introduces specific behavioral strategies for the decisionmaking context that are critical to realizing business outcomes and identifying the key observations and challenges that managers face that affect value creation along dimensions of firm activities.
hdl:10398/9660
Keywords: 650